African American male law enforcement executive perspectives on police-involved shootings of unarmed African American males - Holloman, Lamont (Kansas State University, 2022)
A significant gap exists in the literature concerning African American law enforcement executives (AALEEs). Additionally, there is no existing literature concerning AALEEs' perspectives on police-involved shootings of unarmed African American males. When police officers use deadly force, it is often attributed to the victim's behavior, failure to comply with the police officer's commands, or the victim's criminal history(Peeples, 2020). However, at no point the use of lethal force by police officers are attributed to officers' behavior, departmental policies, or training until the incident reaches the court system. Lethal force by police officers brings about an incredible amount of questioning by the general public and politicians. Police-involved shootings of unarmed African American males receive the most significant attention, to the point of protests, demands for answers, and social distrust. The U.S. Justice Department's unsuccessful attempts to track police-involved shootings limited the researcher to seek other published sources for statistical data. The researcher used The Washington Post and the Society Crime & Law Enforcement sites to gather statistical data on the police-involved shootings of unarmed individuals. This qualitative narrative inquiry explored the viewpoints of AALEEs on police-involved shootings of unarmed African American males. The theoretical framework leaned on the critical race theory (CRT). The research sample included six AALEEs from five police departments. The common comparison was used to analyze the semi-structured interviews, two group discussions, observations, and coding for the findings. The researcher's use of triangulation assisted in ensuring the value of the study. The emergent themes and sub-themes aligned with the theoretical framework to answer the research questions. The findings of this study indicate that better recruitment and hiring processes, diversity training, departmental policy changes, and working as correctional officers before working as police officers on the street could reduce the police-involved shootings of unarmed African American males.
Keywords: African American; Law enforcement executive; Police-involved shootings; Unarmed African American males; Critical race theory